PELATIHAN PENGELOLAAN DATABASE DESA UNTUK MENINGKATKAN KINERJA PERANGKAT DESA KRANGGAN KECAMATAN GEGER KABUPATEN MADIUN - Suprapto, Edy; Murtafiah, Wasilatul; Apriandi, Davi; Setyansah, Reza Kusuma (UNIVERSITAS PGRI MADIUN, 2016)
The purpose of this activity IbM program is to help facilitate the management of village database particular use of information technology by using Microsoft Access. Currently in the village administration is still largely in the form of written records form (manual). Through the utilization of training computer-based applications, is expected to help support the management of the village administration to become more convenient, efficient and effective. IbM activity is carried out by providing training to the village on how to use information technology for database management village. The technology used is the application of system administration using Microsoft Access, which begins with the introduction phase of Microsoft Word and Microsoft Excel as basic training, further d i re c t e d t o u s e M i c ro s o f t A c c e s s p ro g r a m m i n g l a n g u a g e w i t h a s i m p l e s t a g e . Based on the results of community service that has been implemented, the following conclusions can be drawn: 1) Community service activities by the team can be conducted properly and smoothly; 2) Training participants consisting of 6 people, 5 of them have the ability to grasp in the category of medium (83.33%) and one person has the ability to grasp in the category of low (16.67%); 3) Making village database using Ms.Access not been up and still in the early stages of introduction. This is due to the low capacity of participants' understanding of the basic concepts of training materials and the allocation of limited time.